SOME CHARACTERISTICS OF ENSURING FOOD SAFETY IN UZBEKISTAN - Matjonov, Bekjon (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
This article is devoted to Food safety and its peculiarities in our country. In particular, the article covers the work done to ensure Food safety in Uzbekistan on the basis of practical analysis and provides conclusions and recommendations.